Analysis of a series of urban-scale chlorine dispersion experiments and implications on indoor health consequences. (1st September 2019) - Sohn, Michael D.; Delp, William W.; Fry, Richard N.; Kim, Yang-Seon
Abstract: In the United States, industrial compounds are routinely transported by rail in pressurized vessels, often near urban areas. A rupture of a vessel, for example due to a derailment, can result in the rapid release of a liquid-aerosol-gas mixture. The health consequences of such a release, especially close to population centers, are not well understood. To address this question, a series of controlled experimental releases of pressurized chlorine (Cl2 ) was conducted at the Dugway Proving Ground (Dugway, Utah). Each trial consisted of the sudden breach of a tank containing at least 4, 500 kg (kg) of pressurized liquid Cl2 . In this paper, we report on measured Cl2 concentrations in three test structures downwind of the release. Based on these data, we estimate the indoor-outdoor exchange, transport through a multi-room structure, and the first-order loss rate due to reaction or sorption. This loss rate is particularly important for consequence assessment. For example, in a mobile office with a ventilation rate of about three air changes per hour, the reaction loss rate was approximately 2.5 h −1 . This accounts for a nearly 20 percent reduction in toxic load to indoor occupants. Finally, the paper discusses the modeling and analysis of a typical urban hazard assessment. Highlights: In 2015 and 2016, a series of controlled release experiments of pressurized chlorine (Cl2 ) was conducted. An experiment consisted of the sudden breaching of a tank containing greater than 4, 500 kg (kg) of pressurized liquid Cl2 . The measurement of the Cl2 plume's transport through an array of downwind structures. This paper reports the results of an experiment that is unlikely to be conducted often. The reaction between the gas and indoor surfaces is important for hazard and consequence assessment. The current study found that total Cl2 gas loss was faster than the trailer's air change rate.